1997
DOI: 10.1007/s001340050374
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Does continuous heparinization influence platelet function in the intensive care patient?

Abstract: Continuous administration of heparin with an average dose of approximately 500 U/h did not negatively influence platelet function in the trauma patients. Recovery from reduced platelet function in the sepsis group was not affected by continuous heparinization. Thus, continuous heparinization with this dose appears to be safe with regard to platelet function in the intensive care patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…In agreement with some previous reports [18,19], we observed decreased agonist‐induced platelet aggregation in the septic patients. Moreover, flow cytometry confirmed this aggregation defect, demonstrating concomitant alteration in the GPIIbIIIa integrin conformational changes with decreased avidity for the PAC‐1 antibody and fibrinogen binding in the platelets of the septic patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with some previous reports [18,19], we observed decreased agonist‐induced platelet aggregation in the septic patients. Moreover, flow cytometry confirmed this aggregation defect, demonstrating concomitant alteration in the GPIIbIIIa integrin conformational changes with decreased avidity for the PAC‐1 antibody and fibrinogen binding in the platelets of the septic patients.…”
Section: Discussionsupporting
confidence: 93%
“…However, sepsis‐generated cytokines do not seem to activate human platelets either directly or via thrombin [17]. In clinical studies, several investigators have reported decreased platelet aggregability during sepsis [18,19], whereas Gawaz et al . [20] noted increased platelet aggregability.…”
Section: Introductionmentioning
confidence: 99%
“…Determining the response to heparin prior to its use may be available for predicting the development of heparin-induced aggregates in circulation and avoiding unexpected platelet sequestration and consumption especially in patients with thromboembolic disease. Thus, evaluating the response to heparin may improve the safety of heparin treatment in intensive-care patients [13,21].…”
Section: Discussionmentioning
confidence: 99%